MENINGKATKAN MOTIVASI DAN PENCAPAIAN HASIL BELAJAR MAHASISWA DALAM MATAKULIAH BAHASA INGGRIS TEKNIK - Jufrizal Jufrizal; Elisna Elisna (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
The lack of motivation and result of teaching-learning process obtained by the students are the problems faced by technical study programs, including the one at the Faculty of Engineering of Universitas Negeri Padang. This paper discusses the actions done through classroom action research as the attempt to raise the students’ motivation and the result of teaching learning process. The object of the research was the students of D3 regular program of electrical engineering in the academic year of 2005/2006. The result of the research shows that a set of actions, namely: (i) attracting the students to discuss the nature of Technical English subject; (ii) improving and correcting the students’ attitude and perception towards Technical English subject; (iii) applying teaching method and techniques based on natural-constructivism approach; (iv) varying techniques and materials of teaching; (v) using modern equipments, materials, instruments, and facilities effectively, could raise the students’ motivation and their result of teaching-learning process of Technical English subject.